The Newspaper Chapter: A Mirror Reflecting An Yinghua's Journalistic Philosophy—A Brief Discussion of “From West to East: The Newspaper Chapter” - SHI, Xin (Journal of Research for Christianity in China (JRCC), 2025)
As Ernst Faber's representative work and breakthrough publication, From the West to the East concentrates the political, cultural, economic, and religious ideas of early missionaries alongside their geographical and scientific knowledge. Among its contents, the essay “On Newspapers” is regarded as the book's essence and distillation, comprehensively reflecting Hua's journalistic philosophy: the necessity of establishing a “newspaper industry” and the comprehensive qualities required of “journalists”; the dual social and political functions of newspapers. In essence, whether viewed as cultural invasion or the dissemination of civilization, whether aimed at spreading the Pope's teachings or saving all beings, missionaries like Hua, who came to China, effectively introduced modern newspaper concepts and publishing models. They propelled the advancement and evolution of China's journalism industry.
Keywords: From West to East The Newsprint Chapter Ernst Faber Understanding the World Breaking Through Barriers to Seek Communication